2021
DOI: 10.1088/1361-6668/abceb2
|View full text |Cite
|
Sign up to set email alerts
|

Successful DC current limitation above 100 Vm−1 for 50 ms using HTS tapes with critical currents exceeding 750 A/cm-width

Abstract: High-voltage direct current transmission systems are expected to allow the transmission of huge volumes of electricity over long distances. The use of superconducting fault current limiters (SFCLs) based on second-generation (2G) high-temperature superconductor (HTS) coated conductors (CCs) is a promising solution to mitigate fault currents in DC transmission systems. To fabricate a SFCL whose size remains acceptable, which means minimizing the length of the HTS tape used, the tape must sustain a high electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The model used to perform the simulations is a modified version of the 3D model described in [6]. It has been implemented in the COMSOL Multiphysics 5.5 software package and uses two modules, namely the Electric Currents and Heat Transfer in Solids modules.…”
Section: Description Of the Numerical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The model used to perform the simulations is a modified version of the 3D model described in [6]. It has been implemented in the COMSOL Multiphysics 5.5 software package and uses two modules, namely the Electric Currents and Heat Transfer in Solids modules.…”
Section: Description Of the Numerical Modelmentioning
confidence: 99%
“…Increasing the electric field allows us to limit the length of the REBCO tape required, thus reducing the footprint and cost of the SFCL [5]. In particular, it was shown that soldering a 500 µm thick Hastelloy shunt on a REBCO tape (I c > 800 A cm −1 width at 77 K, self-field) allowed the tape to sustain an electric field over 100 V m −1 for 50 ms [6].…”
Section: Introductionmentioning
confidence: 99%
“…The current limitation tests shown here were taken during the European H2020-FASTGRID project which goal was to develop the best 2G HTS CC architecture for a superconducting fault current limiter (FCL) operating in a DC electrical network [5]. Large tape samples (⩾12 cm) were tested in DC fault current conditions using a setup similar to the one described in [44]. A voltage source was connected to both ends of samples with copper blocks held by bolts and screws.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Specific architectures have been designed, known as coated conductors (CC). 5 Although several companies are able to market CC, [6][7][8][9][10][11][12] low-cost and robust fabrication methods that guarantee sufficiently small cost/performance ratios are essential and only few are available. Chemical solution deposition (CSD) methods have demonstrated low cost and fine capabilities in the fabrication of REBCO superconducting films.…”
Section: Introductionmentioning
confidence: 99%